AKTIVITAS ANTIOKSIDAN PADA KU LIT BUAH, BIJI, DAN DAGING BUAH ALPUKAT (PERSEA AMERICANA MILL.) DENGAN METODE DPPH DAN FRAP - Junitia, Gloria
Free radical are molecules or molecular fragments containing a single unpaired electron. Compounds that can reduce the negative effects of free radicals are referred as antioxidants. Various plants are known to have antioxidant activity, such as avocado (Persea americana Miller). The objectives of this research were to study antioxidant activity of peel, seed, and flesh extracts of avocado by DPPH and FRAP methods; determine total phenolic and flavonoid content; analyze the correlation between total phenolic and flavonoid with AAI DPPH and FRAP; analyze the correlation between two antioxidang testing methods. Sample was extracted by reflux using n-hexane, ethyl acetate, and ethanol. Determination of total phenolic content (TPC) and total flavonoid content (TFC), AAI DPPH, and FRAP were performed by UV-visible spectrophotometry. Correlation of TPC and TFC with AAI DPPH and FRAP and also correlation between two methods were conducted by Pearson’s method. The ethanol seeds extract gave the highest TPC (11.549 ± 0.561 g GAE/100 g), while the highest TFC for n-hexane pulp extract (8.041 ± 0.221 g QE/100 g). AAI DPPH in the range of 0.815-64.091 while FRAP 1.649-33.147. In general, TPC in peel, seed, and flesh extracts of avocado had positive and significant correlation with AAI DPPH and FRAP. The values of AAI DPPH and FRAP showed positive and significant correlation. In general, peel, seed, and flesh extracts of avocado had strong to very strong antioxidant by DPPH and FRAP methods. In general, TPC of all samples contributed to antioxidant activities by DPPH and FRAP methods. DPPH and FRAP methods showed linear results in antioxidant activities of peel, seeds, and flesh extracts of avocado.